Keasaman minuman ringan menurunkan kekerasan permukaan gigi (Acidity of soft drink decrease the surface hardness of tooth) - Edhie Arif Prasetyo (Dental Journal (Majalah Kedokteran Gigi), 2005)
Acidity can bring about tooth erosion. A laboratory experiment about soft drink acidity to the hardness of tooth surface was done. The purpose of the study was to investigate the surface hardness of the tooth surface after immersion in some kinds of soft drinks. Thirty maxillary premolars were randomly divided into three groups. The first group was immersed in aqua, pH 7.6, the second group in the tea, pH 6,7 and the last group in Cola pH 2,5 for 30, 60 and 120 minutes. The surface hardness measurement was done before and after immersion using micro Vickers hardness tester. The achieved data were analyzed using ANOVA followed by HSD. It was concluded that the immersion in soft drink for 120 minutes could decrease the surface hardness of tooth.